Pengaruh Inflasi Dan Pertumbuhan Ekonomi Terhadap Tingkat Pengangguran Di Indonesia Periode 2001-2017 - Rts. Ivo Tri Aulia; Siti Hodijah; Etik Umiyati (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The creation of jobs as a real impact of development policies that have been implemented in determining the success of economic development that occured in a country. The purpose of this study is to determine the effect of inflation and economic growth on the unemployment rate in Indonesia. The type of data used in this study is secondary data in the form 2001-2017 in Indonesia, with a method of multiple linear regression data analysis and analysis of development models. The results of the study with a significant level of 10% indicate that Simultaneously the variables of inflation and economic growth have a significant effect on the variable unemployment rate in Indonesia. In fact, economic growth variables have no significant effect on the unemployment rate while the inflation variable has a significant effect on the unemployment rate. R-square 0.280170, this means that the unemployment rate in the period 2001-2017 in Indonesia is influenced by inflation and economic growth while the rest is explained by other factors not discussed in this model. The results of the analysis in development show that the inflation and economic growth variables experience fluctuating developments.